Environmental parameters drive the phytoplankton community structure: a case study in Baghdad Tourist Island Lake, Iraq - Wahhab, Taibat A.; Hassan, Fikrat M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Phytoplankton community is a model for of monitoring  aquatic systems and interpreting the environmental change in aquatic systems. The present study aimed to forecast environmental parameters that drive the change of phytoplankton community structure in the lake. The present study was carried out in Baghdad Tourist Island Lake (BTIL) for the period From October 2021 to May 2022. The study included the quality and quantity of phytoplankton, moreover, the highest and lowest value of the physical and chemical parameters were (Water temperature (13-30 °C), Light penetration (94-275cm), electric conductivity (837-1128 µS/cm), salinity (0.5-0.7 ‰), pH (7-8.2), total alkalinity (126-226 mg CaCO3/L), total Hardness (297-395 mg CaCO3/L), Calcium (62-98 mg/L), Magnesium (59-75mg/L), Sodium (45-77 mg/L), Potassium (4-9 mg/L), dissolved oxygen (6-9 mg/L), total dissolved solids (586-777 mg/L), total phosphorus (0.1-0.7 mg/L), total nitrogen (0.2-3 mg/L). Monthly samples were taken from the subsurface water from three sampling sites in the Lake and the results and presented as dry and wet seasons. A total of 127 algal taxa was identified in the dry and wet seasons with the dominancy of diatoms (Nitzschia, Gomphonema, Navicula, Ulnaria) and followed by Cyanophyceae (Oscillatoria, Merismopedia) and Chlorophyceae (Cladophora), while Dinophyceae (Ceratium, Gymnodinium), and Euglenophyceae (Euglena) were uncommon. The lowest total cell number of phytoplankton was 221cell*104 /L in the first site during the wet season, while the highest total cell number of phytoplankton was recorded at the third site with 323×104 cells/L in the dry season. The Canonical Correspondence Analysis (CCA) showed the impact of environmental parameters on phytoplankton community structure. Therefore, the changes in phytoplankton species were noticed in the present study in comparison with previous periods and this finding is a warning of alteration in the environmental condition of the lake.